PERAN PROFITABILITAS ATAS PENGARUH BOARD GOVERNANCE TERHADAP SUSTAINABILITY REPORT QUALITY - Vinola Herawaty; Nadya Lambintara; Florus Daeli (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
The purpose of this study was to find out the effect of profitability on the relation between Board Governance and Sustainability Report Quality (SRQ) from banking companies listed on Indonesian Stock Exchange. This study used information from Sustainability Report and Annual Report published by each company during period of 2015 to 2019. The sampling method used in this study was purposive sampling, with samples that meet the sample selection criteria came from 11 banking companies, so the total samples in this study were 55 samples. Independent variables used in this study are size of board directors, proportion of independent commissioners, age of board’s members and women on the company’s board, while moderating variable is profitability (ROA). The analysis used in this study are multiple regression analysis and confirmatory factor analysis using the SPSS program to determine the dependent variable, Sustainabilty Report quality. The results showed that board of directors’ size and involvement of women on the company’s board had positive effects on the SRQ. Meanwhile proportion of independent commissioners and ages of board’s members had showed no effect on SRQ. The profitability strengthened the relation between board of directors’ size and the SRQ while it did not moderate the relation between other variables and SRQ. Originality of this study is that the authors add to the literature by answering the question of whether Board Governance is an effective way to increase SRQ and whether profitability strengthens the influence of board governance to SRQ in Indonesian Banking industry.